Determining design criteria to reduce power and cost in filling high-pressure oxygen cylinders directly from cryogenic air separation plants. (June 2021) - Singla, Rohit; Chowdhury, Kanchan
Highlights: Cryogenic air separation plants filling oxygen at 150 bar cylinders are simulated. Replacing coil tube by plate fin heat exchanger reduces power by 6–8%. Internal compression plants consume 17% higher power than external compression ones. Internal compression plants spend 9% lower capital than externally compressed ones. 29% air compressed at 100 bar can gasify pumped LOX at the lowest hourly cost. Abstract: Cryogenic air separation plants produce pressurized oxygen gas at 150 bar and 99.8% purity to fill oxygen cylinders directly. It is either produced by compression in oxygen compressor (external compression) or pumping and vaporizing liquid oxygen in main heat exchanger by incoming air (internal compression). Small and medium-scale plants differ in the types of main heat exchanger, compression and expansion devices owing to limitations of market availability. Levelized cost of production of oxygen gas is about 9% less in external compression, though internal compression process is far more fire-safe. Design and operating parameters applicable for internal compression plants supplying oxygen at 40 bar cannot be extended to 150 bar plants due to the differences of fluid properties between super-critical and sub-critical oxygen. UA (surface area times overall heat transfer coefficient) of main heat exchangers, flow and pressure of incoming air are optimized for minimum capital and operating costs. If the chosen flow and pressures deviate substantially from the optimum points, size of main heat exchanger may even increase five-fold. Ideally, 27–29% of total air intake should be compressed between 110 and 100 bar in a medium-scale internal compression plant to keep levelized cost of production at the minimum.